Forests and Forestry in India - Qureshi, I. M. (Indian Forester, 1969)
Forests constitute one of the most important natural resources which play vital role in the socio-economic development of the country and in the provision of a variety of goods and services whose conservation, and management in perpetuity is essential for the welfare of the people.Forests of India perform a multiple role. productive, protective, bio-esthetic and recreational apart from being of high biological and scientific value. The total land area of the country is 326.8 million ha of which forests occupy 75.3 million ha, i.e., 28.1 % (of which about 6% are coniferous forests and the rest broad-leaved) of the land area in contrast to agriculture which occupies about 48%. The role of forests in the protection of catchments and of agriculture lands from floods, soil erosion and in maintenance or fertility is therefore great. Equally important is the contribution of forests towards development of various wood-based industries essentially required for the overall economic development of the country. The forests of the country are also the habitat of a variety of fauna whose preservation and conservation is of great importance. The population of the country (estimates for mid year 1968 is about 524 million. Thus, India has over 15% of the world's population with only, 1.8% of the world's forests to cater to ever increasing diverse requirements both for local consumption and industrial develoment. Further, out of 75 million ha of forests, as much as 10 million ha or 13.3 % is under protection forests which occupy hilly and mountainous regions or are located on strategic areas where vegetation is solely required for protective functions. Of the remaining area, only 59.2 million ha are merchantable which is about 78.6% of the total forest land. Even in this merchantable forest land most of the area is worked under silvicultural systems which ensure adequate protection to fauna and flora as c1earfelling for plantations is limited to very small percentage. Taking latest figures the man-made forets cover only 1.7% of the total forest area or 1.8 million ha of plantations.The management of forests is in tune with the objectives and concepts of nature conservation which according to IUCN is defined as "The rational use of earth's resources to achieve the highest quality of living for mankind", which of course,has to be in perpetuity.